Ragots, rumeurs, légendes urbaines, et e-canulars : vers un éclaircissement des genres - Van de Winkel, Aurore; Reilly, Ian (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2014)
This essay examines the ubiquity of cultural forms such as gossip, rumours, urban legends, and hoaxes. This study addresses each cultural form as genre, pointing to their overlapping features and characteristics. In what follows, the authors explore each genre’s key practices, practitioners, motivations, and social settings in the interests of unravelling of the oft misunderstood relationships among these and other related forms. The essay situates these forms and practices as vibrant, compelling, and complex forms of discourse that initiate dialogue and deliberation in numerous settings to a broad (if amorphous) public.